Sampling in Times of High Immigration: The Survey Process of the IAB-BAMF-SOEP Survey of Refugees - Simon Kühne; Jannes Jacobsen; Martin Kroh (Survey Methods: Insights from the Field, 2019)
Over the course of 2013 to 2016, over one million asylum seekers arrived in Germany, around 890,000 of them in 2015 alone. The growing refugee population posed a major challenge for Germany's policy makers, civic administrators, and society at large, in finding new approaches to registration procedures, housing, and social and economic integration. To design policies and programs that meet these needs, government administrators, politicians, and the public require robust analyses of the accompanying social and demographic changes based on timely, valid, and reliable empirical data. Yet despite the urgent need for quantitative data on this target group, survey organizations and data collection agencies had little experience gaining access to the target population and approaching and surveying them effectively. In late 2015, when the influx reached its peak, the Institute for Employment Research (IAB), the Migration, Integration and Asylum Research Center at the Federal Office for Migration and Refugees (BAMF-FZ), and the Socio-Economic Panel (SOEP) joined together in a cooperative longitudinal project to survey a nationwide random sample of refugee households in Germany: the IAB-BAMF-SOEP Survey of Refugees. In this paper, we summarize the sampling and fieldwork design as well as the challenges faced in the IAB-BAMF-SOEP Survey of Refugees. We discuss the sequential strategy applied for sampling recent refugees and asylum seekers who arrived in Germany, particularly in 2015, in such large numbers that proper registration was delayed, and in many cases their initial accommodations were only temporary. Moreover, the paper discusses alternative survey instruments introduced for the difficult-to-interview population of the IAB-BAMF-SOEP Survey of Refugees, including translated questionnaires and audio files.
Keywords: 330; Complex samples; Nonresponse; Rare populations; Sampling design